High-resolution imaging of dietary lipids in cells and tissues by NanoSIMS analysis[S] - Haibo Jiang; Chris N. Goulbourne; Angelica Tatar; Kirsten Turlo; Daniel Wu; Anne P. Beigneux; Chris R.M. Grovenor; Loren G. Fong; Stephen G. Young (Journal of Lipid Research, 2014)
Nanoscale secondary ion MS (NanoSIMS) imaging makes it possible to visualize stable isotope-labeled lipids in cells and tissues at 50 nm lateral resolution. Here we report the use of NanoSIMS imaging to visualize lipids in mouse cells and tissues. After administering stable isotope-labeled fatty acids to mice by gavage, NanoSIMS imaging allowed us to visualize neutral lipids in cytosolic lipid droplets in intestinal enterocytes, chylomicrons at the basolateral surface of enterocytes, and lipid droplets in cardiomyocytes and adipocytes. After an injection of stable isotope-enriched triglyceride-rich lipoproteins (TRLs), NanoSIMS imaging documented delivery of lipids to cytosolic lipid droplets in parenchymal cells. Using a combination of backscattered electron (BSE) and NanoSIMS imaging, it was possible to correlate the chemical data provided by NanoSIMS with high-resolution BSE images of cell morphology. This combined imaging approach allowed us to visualize stable isotope-enriched TRLs along the luminal face of heart capillaries and the lipids within heart capillary endothelial cells. We also observed examples of TRLs within the subendothelial spaces of heart capillaries. NanoSIMS imaging provided evidence of defective transport of lipids from the plasma LPs to adipocytes and cardiomyocytes in mice deficient in glycosylphosphatidylinositol-anchored HDL binding protein 1.